PENGARUH MODAL, TENAGA KERJA, LUAS LAHAN DAN TEKNOLOGI TERHADAP PRODUKTIVITAS DAN PENDAPATAN PETANI BERAS MERAH - Prapnuwanti, Ni Putu Ias; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 5 (2021): VOL 10 NO 5, MEI 2021 (1774 - 2222), 2021)
The agricultural sector is a sector that has a very important role in the economy. This study aims to analyze the effect of capital, labor, land area, technology on productivity and income of red rice farmers in Penebel District, Tabanan Regency, Bali Province. The data used in this study are primary data, namely by distributing questionnaires to red rice farmers in Penebel District, Tabanan Regency. The population used in this study were all red rice farmers in Penebel District, Tabanan Regency, amounting to 950 people. The number of samples used is as much as 90 brown rice farmers, using the technique of determining the sample by proportional random sampling. The analysis technique used in this study is path analysis. The results showed that capital, labor, land area and technology had a positive effect on the productivity of brown rice farmers in Penebel District, Tabanan Regency, Bali Province. Capital, labor, land area, technology and productivity have a positive effect on the income of red rice farmers in Penebel District, Tabanan Regency, Bali Province. There is an indirect influence between capital, labor, land area and technology on productivity to the income of red rice farmers in Penebel District, Tabanan Regency, Bali Province.